Approximating one-dimensional coupled shallow water equation for predicting tsunami wave propagation using new semi-implicit method - Siti Maryam Hafiza, Mohd Kanafiah (Universiti Malaysia Perlis (UniMAP), 2016)
Master of Science in Engineering Mathematics